Amphibia, Anura, Hylidae, Dendropsophus melanargyreus (Cope, 1887): Distribution extension, new state record and geographic distribution map - da Silva, Fernando Rodrigues [UNESP]; do Prado, Vitor Hugo Mendonça [UNESP]; Rossa-Feres, Denise de Cerqueira [UNESP] (Pensoft Publishers, 2010)
We present the first record of Dendropsophus melanargyreus for the state of São Paulo and a distribution map for this species. This new record represents the southeastern limit of distribution, which is 106 Km from the nearest locality previously recorded for this species and is the fourth new register of anuran to northwestern region of São Paulo in the last two years, increasing species list of the region from 33 to 36 species. This results evidence the importance of this region as priority area for inventory. © 2010 Check List and Authors.